(untitled) (Global Journal of Computer Science and Technology, 2014)
Vehicular Ad-hoc Networks VANETs are major popular wireless environment for Intelligence Transport Systems ITS This paper concentrates on Location Identification and Driver Safety LIDS Location identification is mapping out by using RFID Radio Frequency Identification technology to recognize the current location and also corresponding surrounded areas The additional feature to be included is to control the speed of vehicle when ever vehicle crosses school and hospital zones For driver safety can be carried out using grip force sensor and eye-ball sensor Driver s drowsiness is detected by the sensors and alerts the buzzer and stops when ever driver comes to normal state and pressing reset button The complete system is controlled by an effectual low cost version of 8051 microcontroller AT89S52 On the whole LIDS suits well for safety vehicle system The implementation results show better performance than already existing methods